Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

A tailored negative electrode material with specific graphite particles and low crystallinity carbon coating enhances lithium-ion batteries' pulse charging, low-temperature performance, and high-temperature stability, addressing the challenges of automotive applications.

JP2025012123AActive Publication Date: 2025-01-24RESONAC CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023114713
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-24
Estimated Expiration
2043-07-12

AI Technical Summary

Technical Problem

Lithium-ion secondary batteries for automotive applications require improved pulse charging characteristics, low-temperature charging properties, and high-temperature storage characteristics to meet the demands of electric vehicles and hybrid electric vehicles, while maintaining high energy density and stability under varying environmental conditions.

Method used

A negative electrode material comprising specific graphite particles with controlled particle size distribution, density, and surface coating of low crystallinity carbon, combined with a blend of graphite particles of varying hardness to optimize electrode density and electrolyte penetration, enhancing input/output characteristics and stability.

Benefits of technology

The solution results in lithium-ion secondary batteries with superior pulse charging capabilities, low-temperature performance, high-temperature storage retention, and stable discharge load characteristics, while maintaining high energy density and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012123000008
    Figure 2025012123000008
  • Figure 2025012123000009
    Figure 2025012123000009
  • Figure 2025012123000001
    Figure 2025012123000001
Patent Text Reader

Abstract

To provide a negative electrode material for a lithium ion secondary battery that has excellent discharge load characteristics, low-temperature charging characteristics, high-temperature storage characteristics, and pulse charging characteristics, as well as a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery that use the same.SOLUTION: A negative electrode material for a lithium ion secondary battery includes first graphite particles that satisfy specific conditions of apparent density and linseed oil absorption, and second graphite particles that satisfy specific conditions of D0.1 and linseed oil absorption, the amount of the second graphite particles are 10 mass% to 55 mass% with respect to the total mass of the graphite particles, the first graphite particles are secondary particles composed of a plurality of natural graphite particles, at least a portion of the surface of which is coated with a carbon material having a lower crystallinity than the natural graphite particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. [Background technology]

[0002] Lithium-ion secondary batteries are small, lightweight, and have a high energy density, and are widely used in electronic devices such as notebook PCs, mobile phones, smartphones, and tablet PCs. 2 In the context of environmental issues such as global warming caused by emissions, clean electric vehicles (EVs) that run only on batteries, hybrid electric vehicles (HEVs) that combine gasoline engines with batteries, etc. have become widespread. Recently, they have also been used for power storage, and their applications are expanding to a wide range of fields.

[0003] The performance of the negative electrode material of a lithium-ion secondary battery greatly affects the characteristics of the lithium-ion secondary battery. Carbon materials are widely used as materials for the negative electrode material of lithium-ion secondary batteries. Carbon materials used for negative electrode materials are roughly classified into graphite and carbon materials with lower crystallinity than graphite (amorphous carbon, etc.). Graphite has a structure in which hexagonal mesh planes of carbon atoms are regularly stacked, and when graphite is used as the negative electrode material of a lithium-ion secondary battery, the insertion and desorption reactions of lithium ions proceed from the ends of the hexagonal mesh planes, and charging and discharging are performed.

[0004] Amorphous carbon has irregular stacking of hexagonal mesh faces or does not have hexagonal mesh faces. Therefore, in a negative electrode material using amorphous carbon, the insertion and desorption reaction of lithium ions proceeds on the entire surface of the negative electrode material. Therefore, it is easier to obtain a lithium ion battery with better input / output characteristics than when graphite is used as the negative electrode material (see, for example, Patent Document 1 and Patent Document 2). On the other hand, amorphous carbon has lower crystallinity than graphite, and therefore has lower energy density than graphite. Taking into consideration the characteristics of carbon materials as described above, a negative electrode material has been proposed that improves input / output characteristics while maintaining a high energy density by combining amorphous carbon with graphite, and reduces surface reactivity by coating graphite with amorphous carbon, thereby improving input / output characteristics while maintaining good initial charge / discharge efficiency (see, for example, Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 4-370662 [Patent Document 2] Japanese Patent Application Publication No. 5-307956 [Patent Document 3] International Publication No. 2012 / 015054 Summary of the Invention [Problem to be solved by the invention]

[0006] Lithium-ion secondary batteries for automotive applications such as EVs and HEVs are required to have high input / output characteristics (i.e., excellent discharge load characteristics) in order to charge regenerative energy power and discharge it for driving the motor. Furthermore, automobiles are easily affected by the outside temperature, and lithium-ion secondary batteries are exposed to harsh conditions in summer and winter. Therefore, lithium-ion secondary batteries for automotive applications are required to have both low-temperature charging characteristics and high-temperature storage characteristics. Furthermore, in recent years, lithium-ion secondary batteries for automotive applications are also required to have pulse charging characteristics in order to shorten the charging time.

[0007] An object of one aspect of the present disclosure is to provide a negative electrode material for lithium ion secondary batteries that has excellent discharge load characteristics, low-temperature charging characteristics, high-temperature storage characteristics, and pulse charging characteristics, as well as a negative electrode for lithium ion secondary batteries and a lithium ion secondary battery using the same. [Means for solving the problem]

[0008] Specific means for solving the above problems are as follows. <1> First graphite particles satisfying the following conditions 1A and 1B; Second graphite particles satisfying the following conditions 2A and 2B, The amount of the second graphite particles is 10% by mass to 55% by mass based on the total mass of the graphite particles; A negative electrode material for lithium ion secondary batteries, wherein the first graphite particles are secondary particles composed of a plurality of natural graphite particles, and at least a portion of the surface of the first graphite particles is coated with a carbon material having a lower crystallinity than the natural graphite particles. Condition 1A: The loose apparent density T1 measured by the static method is 0.60 g / cc or more, the apparent density T2 measured by the 30 tapping method is 0.80 g / cc or more, the apparent density T3 measured by the 250 tapping method is 1.00 g / cc or more, and the value of the compression degree shown by the following formula is 19% or less. Compression ratio (%) = [(T2-T1) / T3] x 100 Condition 1B: Linseed oil absorption is 40mL / 100g to 55mL / 100g Condition 2A: D0.1 in the volume-based particle size distribution is 5 μm or less Condition 2B: Linseed oil absorption is 55mL / 100g to 75mL / 100g <2> The first graphite particles have a volume-based particle size distribution of D10 of 7 μm to 13 μm and D90 of 14 μm to 25 μm; <1> The negative electrode material for lithium ion secondary batteries according to claim 1. <3> D0.1 in the volume-based particle size distribution of the first graphite particles is greater than 5 μm; <1> The negative electrode material for lithium ion secondary batteries according to claim 1. <4> Further comprising third graphite particles satisfying the following conditions 3A and 3B: The third graphite particles are secondary particles composed of a plurality of natural graphite particles, and at least a portion of the surface of the third graphite particles is coated with a carbon material having a lower crystallinity than the natural graphite particles. <1> The negative electrode material for lithium ion secondary batteries according to claim 1. Condition 3A: In the volume-based particle size distribution, the ratio of D50 of the third graphite particles to D50 of the first graphite particles (D50 of the third graphite particles / D50 of the first graphite particles) is in the range of 0.55 to 0.75. Condition 3B: Linseed oil absorption is 40mL / 100g to 55mL / 100g <5> The amount of the third graphite particles is 10% by mass to 25% by mass based on the total mass of the graphite particles; <4> The negative electrode material for lithium ion secondary batteries according to claim 1. <6> <1> ~ <5> 13. A negative electrode for a lithium ion secondary battery comprising: a negative electrode layer comprising the negative electrode material according to any one of claims 1 to 12; and a current collector. <7> <6> A lithium ion secondary battery comprising the negative electrode for lithium ion secondary batteries according to claim 1, a positive electrode, and an electrolyte solution. Effect of the Invention

[0009] In one aspect of the present disclosure, it is possible to provide a negative electrode material for lithium ion secondary batteries that has excellent discharge load characteristics, low-temperature charging characteristics, high-temperature storage characteristics, and pulse charging characteristics, as well as a negative electrode for lithium ion secondary batteries and a lithium ion secondary battery using the same. [Brief description of the drawings]

[0010] [Figure 1] FIG. 13 is a graph showing the relationship between the oil pressure (t) and the electrode density (g / cm3) when pressing the sample electrode. [Diagram 2] FIG. 13 is a graph showing the relationship between the oil pressure (t) and the electrode density (g / cm3) when pressing the sample electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments for carrying out the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, the components (including element steps, etc.) are not essential unless otherwise specified. The same applies to the numerical values ​​and their ranges, and they do not limit the present invention. In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the present disclosure, in which numerical ranges are described in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit of the numerical ranges may be replaced with values ​​shown in the examples. In the present disclosure, when the negative electrode material and the composition contain multiple substances corresponding to each component, the content and amount of each component in the negative electrode material and the composition refer to the total content and amount of the multiple substances present in the negative electrode material and the composition, unless otherwise specified. In the present disclosure, the particle size of each component in the negative electrode material and the composition means the value for a mixture of the multiple types of particles present in the negative electrode material and the composition, unless otherwise specified, when multiple types of particles corresponding to each component are present in the negative electrode material and the composition. In this disclosure, the term "layer" includes cases where the layer is formed over the entire area when the area in which the layer exists is observed, as well as cases where the layer is formed over only a portion of the area. In this disclosure, the term "lamination" refers to stacking layers, where two or more layers may be bonded together or two or more layers may be removable.

[0012] <Anode material for lithium-ion secondary batteries> The negative electrode material for lithium ion secondary batteries (hereinafter also simply referred to as the negative electrode material) of the present disclosure is First graphite particles satisfying the following conditions 1A and 1B; Second graphite particles satisfying the following conditions 2A and 2B, The amount of the second graphite particles is 10% by mass to 55% by mass based on the total mass of the graphite particles; The first graphite particles are secondary particles composed of a plurality of natural graphite particles, and at least a portion of the surface of the first graphite particles is covered with a carbon material having a lower crystallinity than the natural graphite particles. Condition 1A: The loose apparent density T1 measured by the static method is 0.60 g / cc or more, the apparent density T2 measured by the 30 tapping method is 0.80 g / cc or more, the apparent density T3 measured by the 250 tapping method is 1.00 g / cc or more, and the value of the compression degree shown by the following formula is 19% or less. Compression ratio (%) = [(T2-T1) / T3] x 100 Condition 1B: Linseed oil absorption is 40mL / 100g to 55mL / 100g Condition 2A: D0.1 in the volume-based particle size distribution is 5 μm or less Condition 2B: Linseed oil absorption is 55mL / 100g to 75mL / 100g

[0013] As shown in the examples described below, by using the negative electrode material of the present disclosure, a lithium ion secondary battery having excellent input / output characteristics, low-temperature charging characteristics, high-temperature storage characteristics, and pulse charging characteristics can be obtained.

[0014] (First graphite particle) The first graphite particles have a loose apparent density T1 measured by a static method of 0.60 g / cc or more, an apparent density T2 measured by a 30 tap method of 0.80 g / cc or more, and an apparent density T3 measured by a 250 tap method of 1.00 g / cc or more.

[0015] The negative electrode of a lithium ion secondary battery is obtained by forming a coating film on a current collector such as copper foil using a slurry containing a negative electrode material, and then drying the coating film. In order to increase the energy density of lithium ion secondary batteries, it is necessary to increase the packing density of the negative electrode material in the coating film, in other words, to increase the density of the coating film. As a result of careful investigation by the inventors, it was found that a good coating film can be formed when the solids content of the slurry used to form the coating film is sufficiently high, and that a sufficiently high solids content of the slurry can be achieved when the apparent density of the first graphite particles satisfies the above condition. When the apparent density of the first graphite particles satisfies the above condition, the variation in film thickness during coating is small, the amount of binder required to obtain sufficient adhesion strength can be reduced, and the decrease in effective capacity tends to be suppressed.

[0016] Furthermore, when the apparent density of the first graphite particles satisfies the above conditions, the electrode density of the coating film increases, and the pressing pressure required to obtain the target electrode density tends to be reduced. By lowering the pressing pressure, the orientation of the graphite particles in the direction perpendicular to the thickness direction of the negative electrode decreases, making it easier to take in and out lithium ions during charging and discharging. As a result, a lithium ion secondary battery with better input and output characteristics such as low-temperature charging characteristics and discharge load characteristics tends to be obtained.

[0017] The T1 of the first graphite particles is preferably 0.62 g / cc or more, and more preferably 0.65 g / cc or more. The upper limit of T1 is not particularly limited, but may be, for example, 0.80 g / cc or less. The T2 of the first graphite particles is preferably 0.81 g / cc or more, and more preferably 0.82 g / cc or more. The upper limit of T2 is not particularly limited, but may be, for example, 1.00 g / cc or less. The T3 of the first graphite particles is preferably 1.03 g / cc or more, and more preferably 1.05 g / cc or more. The upper limit of T3 is not particularly limited, but may be, for example, 1.20 g / cc or less.

[0018] The value of the degree of compression calculated from the apparent density of the first graphite particles is 19% or less. When the apparent density of the first graphite particles is within the above range, the value of the degree of compression tends to be small. In lithium-ion secondary batteries, the carbon material used as the negative electrode material repeatedly expands and contracts during charging and discharging. Therefore, if the adhesion between the carbon material and the current collector is poor, the carbon material may peel off from the current collector, resulting in a decrease in charge / discharge capacity and a deterioration in cycle characteristics. When the degree of compression of the first graphite particles contained in the negative electrode material is 19% or less, the adhesion between the negative electrode material and the current collector tends to be improved. Therefore, by using the negative electrode material of this embodiment, even when the carbon material repeatedly expands and contracts due to charging and discharging, the adhesion between the carbon material and the current collector is well maintained, and a lithium ion secondary battery with excellent life characteristics such as high-temperature storage characteristics and cycle characteristics tends to be obtained.

[0019] The degree of compression of the first graphite particles is preferably 18% or less, and more preferably 17% or less. The lower limit of the degree of compression is not particularly limited, but may be, for example, 13% or more, or 14% or more.

[0020] The first graphite particles have a linseed oil absorption of 40 mL / 100 g to 55 mL / 100 g. The linseed oil absorption of graphite particles is an index that indirectly quantifies the voids between particles, and it can be determined that the larger the linseed oil absorption value, the more voids there are between the particles. The linseed oil absorption of graphite particles is affected by the particle size, particle size distribution, particle shape, tap density, etc. of the graphite particles. When the linseed oil absorption of the first graphite particles is 40 mL / 100 g or more, there are advantages in that the filling of the negative electrode material does not proceed too much, the thickness of the coating film is less likely to vary depending on drying conditions, etc., and the density is less likely to vary when the coating film density increases due to pressing. Furthermore, since the residual stress due to pressing is small, the negative electrode is less likely to peel off from the current collector, and the input / output characteristics and cycle characteristics tend not to deteriorate. The first graphite particles preferably have a linseed oil absorption of 41 mL / 100 g or more, and more preferably have a linseed oil absorption of 42 mL / 100 g or more.

[0021] When the linseed oil absorption of the first graphite particles is 55 mL / 100 g or less, the amount of fine particles relative to the gaps between the large particles is not too large, and the electrolyte can easily penetrate. Furthermore, the diffusion resistance of lithium ions is reduced, and the overall battery performance, especially the continuous charge acceptance (pulse charge characteristics), tends not to deteriorate easily. The linseed oil absorption of the first graphite particles is preferably 53 mL / 100 g or less, and more preferably 50 mL / 100 g or less.

[0022] The first graphite particles preferably have a D10 in the volume-based particle size distribution within the range of 7 μm to 13 μm and a D90 within the range of 14 μm to 25 μm.

[0023] When the first graphite particles have a D10 of 7 μm or more and a D90 of 14 μm or more, the particles tend not to be too small and the specific surface area not too large, and good charge / discharge efficiency and high discharge capacity tend to be obtained. When the first graphite particles have a D10 of 13 μm or less and a D90 of 25 μm or less, the particles are not too large, and deterioration of input / output characteristics such as low-temperature charge acceptance and discharge load characteristics tends to be suppressed. In addition, deterioration of life characteristics such as high-temperature storage characteristics and cycle characteristics tends to be suppressed. The D10 of the first graphite particles is preferably from 7.1 μm to 12.5 μm, and more preferably from 7.5 μm to 10.0 μm. The first graphite particles preferably have a D90 of 14.5 μm to 24.5 μm, and more preferably have a D90 of 15.0 μm to 20.0 μm.

[0024] The first graphite particles preferably have a D0.1 in the volume-based particle size distribution larger than 5 μm, more preferably 5.2 μm or more, and even more preferably 5.5 μm or more. When the first graphite particles have D0.1 of more than 5 μm, the particles tend not to be too small and the specific surface area not to be too large, and good charge / discharge efficiency and high discharge capacity tend to be obtained. The upper limit of D0.1 of the first graphite particles is not particularly limited, but may be, for example, 10 μm or less, 8 μm or less, or 7 μm or less.

[0025] The first graphite particles preferably have a D50 in the volume-based particle size distribution of 8 μm or more, more preferably 8.5 μm or more, and even more preferably 9 μm or more.

[0026] The first graphite particles preferably have a D50 in the volume-based particle size distribution of 20 μm or less, more preferably 19 μm or less, and even more preferably 18 μm or less.

[0027] In the present disclosure, D0.1, D10, D50 and D90 of graphite particles refer to the particle sizes at which the cumulative frequency of the distribution from the small particle side reaches 0.1%, 10%, 50% and 90%, respectively, in the volumetric particle size distribution. The volumetric particle size distribution is measured by a laser diffraction method.

[0028] The first graphite particles are secondary particles composed of a plurality of natural graphite particles, and at least a portion of the surface of the first graphite particles is covered with a carbon material having a lower crystallinity than the natural graphite particles. At least a part of the surface of the first graphite particles is covered with a carbon material (hereinafter, also referred to as low-crystalline carbon) having a lower crystallinity than natural graphite particles, so that the surface exposure of the graphite particles, which serve as core materials contributing to charge and discharge reactions, is suppressed. As a result, when a lithium-ion secondary battery is produced, the decomposition reaction of the electrolyte on the surface of the negative electrode material is suppressed, and the deterioration of the initial efficiency, cycle characteristics, and pulse charge characteristics tends to be suppressed.

[0029] The amount of low crystalline carbon relative to 100 parts by mass of graphite particles serving as the core material may be, for example, within a range of 1 to 20 parts by mass, or within a range of 1 to 10 parts by mass.

[0030] The first graphite particles are obtained by subjecting natural graphite particles to processing such as spheroidization, pulverization, etc. The shape of the first graphite particles can be spherical, lumpy, etc. Examples of natural graphite used to produce the first graphite particles include scaly graphite, flake graphite, and amorphous graphite. The natural graphite used in the production of the first graphite particles is preferably purified by a purification process. The purification process method is not particularly limited and can be appropriately selected from commonly used purification processes. For example, flotation, electrochemical treatment, chemical treatment, etc. can be mentioned.

[0031] The purity of the natural graphite used to manufacture the first graphite particles is preferably 99.8% or more (ash content 0.2% or less) by mass, and more preferably 99.9% or more (ash content 0.1% or less). A purity of 99.8% or more tends to improve the safety of the battery and improve the battery performance. The purity of the natural graphite can be calculated, for example, by leaving 100 g of graphite in an 800°C furnace in an air atmosphere for 48 hours or more, and then measuring the remaining amount derived from the ash.

[0032] The method for coating the surface of the graphite particles as the core material with low-crystalline carbon is not particularly limited. For example, the method may include a step of heat-treating a mixture containing the graphite particles as the core material and a substance that changes to low-crystalline carbon by heating (hereinafter, also referred to as a precursor of low-crystalline carbon). The precursor of low crystalline carbon is not particularly limited, and examples thereof include pitch, organic polymer compounds, etc. Examples of pitch include ethylene heavy end pitch, crude oil pitch, coal tar pitch, asphalt decomposition pitch, pitch produced by pyrolyzing polyvinyl chloride, etc., and pitch produced by polymerizing naphthalene, etc. in the presence of a super strong acid. Examples of organic polymer compounds include thermoplastic resins such as polyvinyl chloride, polyvinyl alcohol, polyvinyl acetate, and polyvinyl butyral, and natural substances such as starch and cellulose. The precursors of graphite particles and low crystalline carbon serving as core materials used in the production of the first graphite particles may each be of one type alone or two or more types. The temperature at which the mixture containing the graphite particles as the core material and the low crystalline carbon precursor is heat-treated is not particularly limited, but is preferably 900°C to 1500°C in terms of improving the cycle characteristics of the lithium ion secondary battery. In the above method, the content of the graphite particles as the core material in the mixture before the heat treatment is not particularly limited. From the viewpoint of improving the cycle characteristics of the lithium ion secondary battery, the content of the graphite particles as the core material is preferably 90 mass % to 99.9 mass % with respect to the total mass of the mixture.

[0033] The specific surface area (N2 The specific surface area is not particularly limited, but is, for example, 2.5 m 2 / g~5m 2 / g, and 3m 2 / g~5m 2 / g. 2 If the specific surface area is within the above range, the lithium ion secondary battery tends to have a good balance among the initial charge / discharge efficiency, input / output characteristics, and cycle characteristics. Graphite particles N 2 The specific surface area is measured by the method described in the Examples below.

[0034] The R value of the first graphite particles in Raman spectroscopy is not particularly limited, but is preferably 0.2 to 1.0, and more preferably 0.2 to 0.8. When the R value of the first graphite particles is 0.2 or more, there is a tendency that the graphite lattice defects used for the insertion and removal of lithium ions are sufficiently present, and the deterioration of input / output characteristics is suppressed. When the R value of the first graphite particles is less than 1.0, the decomposition reaction of the electrolyte is sufficiently suppressed, and the deterioration of the initial efficiency is suppressed. In the present disclosure, the R value of the graphite particles is determined by Raman spectroscopy measurement. -1 The intensity Ig of the maximum peak near 1360 cm -1 The intensity ratio (Id / Ig) is the intensity ratio Id of the maximum peak in the vicinity of the peak. The R value of the graphite particles is measured by the method described in the Examples below.

[0035] First graphite particle CO 2 The amount of adsorption is not particularly limited, but for example, 0.10 cm 3 / g~0.40cm 3 / g, and preferably 0.10 cm 3 / g~0.30cm 3 / g, more preferably 0.10 cm 3 / g~0.20cm 3 More preferably, CO 2 has a high saturated vapor pressure, and CO 2Because the kinetic energy of the molecules is extremely high, they are unlikely to be adsorbed on the basal plane of the graphite skeleton, which has weak interactions. However, CO is easily adsorbed on the irregularities that occur in lattice defects, i.e., ultra-micropores, due to extremely strong adsorption interactions. 2 It is known that molecules are adsorbed. On the other hand, lattice defects are known to be active sites for oxidation-reduction reactions and to be active in the decomposition reaction of electrolytes due to the lattice disorder and the biased dipole moment, which causes the lattice to become distorted. 2 When the amount of adsorption is within the above-mentioned range, it is believed that excessive decomposition reactions of the electrolyte, etc. can be suppressed while leaving sites for lithium ions to be inserted and removed between the graphite layers. It is also known that the decomposition products of the electrolyte form a solid electrolyte interphase (SEI) film on the active material surface, which becomes a resistance component in the input / output characteristics. Therefore, the CO 2 By setting the adsorption amount within the above-mentioned range and suppressing excessive side reactions such as electrolyte decomposition, excellent input / output characteristics and high-temperature storage characteristics can be obtained. Graphite particles CO 2 The amount of adsorption is measured by the method described in the Examples below.

[0036] Average interplanar spacing of first graphite particle d 002 is not particularly limited, but is preferably, for example, graphite particles in the range of 0.335 nm to 0.339 nm. In particular, from the viewpoint of increasing the charge / discharge capacity, d 002 The average interplanar spacing d is more preferably in the range of 0.335 nm to 0.338 nm, and further preferably in the range of 0.335 nm to 0.337 nm. 002 When graphite particles having a particle diameter in the range of 0.335 nm to 0.337 nm are used, a good lithium ion secondary battery with a large charge / discharge capacity of 330 mAh / g to 370 mAh / g tends to be obtained. Average interplanar spacing of graphite particles d 002 is measured by the method described in the Examples below.

[0037] The range of the average circularity of the first graphite particles is not particularly limited, but is preferably, for example, 0.74 or more, and more preferably 0.80 or more. By having the first graphite particles have an average circularity of 0.74 or more, even if the graphite particles form aggregates due to intermolecular interactions, the localization of the binder and other components absorbed in the gaps between the particles can be suppressed, and an electrode with excellent adhesion tends to be obtained. In addition, since the localization of the binder is suppressed, the increase in the required amount of binder is suppressed. As a result, the decrease in capacity and the decrease in input / output characteristics due to the increase in resistance components tend to be suppressed. Furthermore, a uniform low-crystalline carbon layer is formed on the surface of the graphite particles that serve as the core material, and the variation in the amount of low-crystalline carbon coating between particles tends to be suppressed. As a result, the inside of the negative electrode is suppressed from being divided into harder parts and particles (i.e., a large amount of low-crystalline carbon coating) and softer parts and particles (i.e., a small amount of low-crystalline carbon coating). As a result, the increase in specific surface area due to the occurrence of cracks in the parts with a small amount of low-crystalline carbon coating that cannot withstand the load of the press treatment, and the decrease in high-temperature storage characteristics due to high activation caused by the occurrence of cracks tend to be suppressed. The average circularity of the graphite particles is measured by the method described in the Examples below.

[0038] (Second graphite particles) The second graphite particles have a D0.1 in the volume-based particle size distribution of 5 μm or less. When the D0.1 of the second graphite particles is 5 μm or less, there are sufficient fine particles of the second graphite that fill the gaps of the first graphite particles, which tends to ensure sufficient contact points between the particles, reduce electronic resistance, and suppress deterioration of the overall battery performance. The D0.1 of the second graphite particles is preferably 4.5 μm or less, and more preferably 4 μm or less. The lower limit of D0.1 of the second graphite particles is not particularly limited, but may be, for example, 1 μm or more, or 1.5 μm or more.

[0039] The second graphite particles have a linseed oil absorption of 55 mL / 100 g to 75 mL / 100 g. When the second graphite particles have a linseed oil absorption of 55 mL / 100 g or more, there are sufficient fine particles of the second graphite particles that fill the gaps of the first graphite particles, which tends to ensure sufficient contact points between the particles, reduce electronic resistance, and suppress deterioration of the overall battery performance. When the linseed oil absorption of the second graphite particles is 75 mL / 100 g or less, the amount of fine particles originating from the second graphite particles filling the voids of the first graphite particles is not too large, allowing smooth penetration of the electrolyte. In addition, the diffusion resistance of lithium ions is small, and deterioration of the overall battery performance, especially the continuous charge acceptance (pulse charge characteristics), tends to be suppressed.

[0040] The material of the second graphite particles is not particularly limited, and may be natural graphite or artificial graphite. The natural graphite includes natural graphite that can be used as the first graphite particles. Examples of artificial graphite include resin-based materials such as epoxy resin and phenol resin, pitch-based materials obtained from petroleum, coal, etc., and artificial graphite obtained by burning coke, etc. The second graphite particles may be in the form of secondary particles formed from a plurality of primary particles. The second graphite particles may or may not have at least a portion of their surface coated with low crystalline carbon.

[0041] When natural graphite is used, the method for producing the second graphite particles is the same as the method for producing the first graphite particles. There is no particular limitation on the method for obtaining artificial graphite. For example, raw materials such as resin, naphthalene, anthracene, phenanthroline, coal tar, and tar pitch are calcined in an inert atmosphere at 800° C. or higher to obtain a calcined product of artificial graphite. In this case, the calcined product obtained is pulverized by a known method such as a jet mill, a vibration mill, a pin mill, or a hammer mill, and the particle size is adjusted to produce second graphite particles derived from artificial graphite. In addition, the raw materials may be heat-treated before calcination.

[0042] The D50 in the volumetric particle size distribution of the second graphite particles is not particularly limited. For example, the D50 of the second graphite particles is preferably 15 μm to 25 μm, and more preferably 17 μm to 25 μm. When the D50 of the second graphite particles is 25 μm or less, the discharge capacity, input / output characteristics, and cycle characteristics tend to improve. When the D50 of the second graphite particles is 15 μm or more, the initial charge / discharge efficiency tends to improve.

[0043] The specific surface area (N 2 The specific surface area is not particularly limited, but is, for example, 1.7 m 2 / g~5m 2 / g, and 2m 2 / g~4.5m 2 / g. 2 When the specific surface area is within the above range, a good balance of the initial charge / discharge efficiency, input / output characteristics, and cycle characteristics tends to be obtained.

[0044] Secondary graphite particles CO 2 The amount of adsorption is not particularly limited, but for example, 0.10 cm 3 / g~0.40cm 3 / g, and preferably 0.10 cm 3 / g~0.30cm 3 / g, more preferably 0.20 cm 3 / g~0.30cm 3 / g. 2 When the adsorption amount is within the above range, excessive side reactions such as electrolyte decomposition are suppressed, and excellent input / output characteristics and high-temperature storage characteristics tend to be obtained.

[0045] (Third graphite particles) The negative electrode material of the present disclosure may contain third graphite particles in addition to the first and second graphite particles. By including the third graphite particles in the negative electrode material, a lithium ion secondary battery having high capacity and excellent efficiency when mounted at high density can be obtained.

[0046] The third graphite particles have a ratio of D50 of the third graphite particles to D50 of the first graphite particles (D50 of third graphite particles / D50 of first graphite particles, hereinafter also referred to as particle size ratio) in a volume-based particle size distribution of 0.55 to 0.75. The third graphite particles having a particle size ratio within the above range are finer than the first graphite particles (the particle size ratio is smaller than 1), and therefore tend to be harder graphite particles than the first graphite particles. For this reason, by forming a coating using a negative electrode material containing the third graphite particles, deformation of the particles due to the pressing force for densification is further suppressed. As a result, the permeation path of the electrolyte is sufficiently secured, and the electrolyte tends to permeate smoothly. By setting the particle size ratio of the third graphite particles to 0.55 or more, the coating film does not become too hard, and the tendency for the pressing pressure required to obtain the target electrode density to become high is suppressed, and the electrode density can be well controlled. As a result, the orientation of the graphite particles in the direction perpendicular to the thickness direction of the electrode does not become too high, and the deterioration of input / output characteristics and the deterioration of capacity and efficiency during high-density mounting tend to be suppressed. By ensuring that the particle size ratio of the third graphite particles is 0.75 or less, the coating film does not become too soft, suppressing springback after pressing (the phenomenon in which the material tries to return to its state before pressing), and the electrode density can be well controlled. The particle size ratio of the third graphite particles is preferably 0.60 to 0.75, and more preferably 0.65 to 0.75.

[0047] The third graphite particles have a linseed oil absorption of 40 mL / 100 g to 55 mL / 100 g. When the linseed oil absorption of the third graphite particles is 40 mL / 100 g or more, the gaps between the particles are not too small and the filling does not proceed too much. Therefore, the coating thickness is less likely to vary depending on the drying conditions, and the electrode density is less likely to vary even when pressed at high pressure. Furthermore, the residual stress caused by pressing is small, so the negative electrode is less likely to peel off from the current collector. As a result, the input / output characteristics and cycle characteristics are maintained well. When the linseed oil absorption of the third graphite particles is 55 mL / 100 g or less, the amount of fine particles in the gaps between the first graphite particles and the second graphite particles is not too large, allowing the electrolyte to smoothly penetrate. In addition, the diffusion resistance of lithium ions is small, and deterioration of the overall battery performance, especially the continuous charge acceptance (pulse charge characteristics), is suppressed. In order to further improve the performance of the lithium ion secondary battery, the third graphite particles preferably have a linseed oil absorption of 41 mL / 100 g to 55 mL / 100 g, and more preferably 41 mL / 100 g to 50 mL / 100 g.

[0048] The third graphite particles are secondary particles composed of a plurality of natural graphite particles, and at least a portion of the surface of the particles is covered with a carbon material having a lower crystallinity than the natural graphite particles. For details and preferred embodiments of the secondary particles consisting of a plurality of natural graphite particles and the coating with low crystalline carbon, the description of the first graphite particles can be referred to.

[0049] The above-mentioned preferred embodiments of the first graphite particles can be referred to as preferred embodiments of the third graphite particles.

[0050] (Graphite particle mixing ratio) In the negative electrode material of the present disclosure, the amount of the second graphite particles is 10 mass % to 55 mass % based on the total mass of the graphite particles. The second graphite particles have a wide particle size distribution and include particles larger than the first graphite particles and particles finer than the first graphite particles. By blending the first graphite particles and the second graphite particles with different particle size distributions, the voids between the particles are mutually filled, and the filling state of the resulting negative electrode coating film can be controlled. That is, in the pressing process in the negative electrode manufacturing, the pressing force can be applied uniformly inside the coating film. As a result, the density variation in the thickness direction of the coating film is reduced, and the electrolyte permeates smoothly. In addition, since the first graphite particles are relatively fine particles and at least a part of the surface is coated with low crystallinity carbon, they tend to be harder than the second graphite particles (especially the second graphite particles not coated with low crystallinity carbon). By blending graphite particles with different hardness, such as the first graphite particles and the second graphite particles with different hardness, deformation of the particles when pressed at high pressure is suppressed, the electrolyte permeation path is sufficiently secured, and the electrolyte permeates smoothly.

[0051] In the negative electrode material of the present disclosure, the amount of the second graphite particles is 10% by mass or more relative to the total mass of the graphite particles, so that there are sufficient fine particles originating from the second graphite particles that fill the voids of the first graphite particles, and therefore sufficient contact points between the particles are secured, electronic resistance is small, and deterioration of the overall battery performance is suppressed. In the negative electrode material of the present disclosure, the amount of the second graphite particles is 55% by mass or less relative to the total mass of the graphite particles, so that the relatively soft second graphite particles are unlikely to deform due to the pressing force. This allows the electrolyte to penetrate smoothly, reduces the diffusion resistance of lithium ions, and tends to suppress deterioration of the overall battery performance, especially the continuous charge acceptance (pulse charging characteristics). Furthermore, the amount of coarse particles derived from the second graphite particles is not too large, suppressing local expansion and contraction due to charge and discharge within the electrode. As a result, peeling of the electrode from the current collector is suppressed, and good cycle characteristics are maintained.

[0052] The amount of the second graphite particles is preferably 15% by mass to 55% by mass, more preferably 20% by mass to 55% by mass, and further preferably 25% by mass to 55% by mass, based on the total mass of the graphite particles.

[0053] When the negative electrode material of the present disclosure contains the third graphite particles, the amount of the third graphite particles is preferably 10 mass % to 25 mass % based on the total mass of the graphite particles.

[0054] When the amount of the third graphite particles contained in the negative electrode material is 10% by mass or more based on the total mass of the graphite particles, there are sufficient fine particles derived from the second graphite particles and the third graphite particles that fill the voids of the first graphite particles, so that there are sufficient contact points between the particles, the electronic resistance is small, and deterioration of the overall battery performance tends to be suppressed.

[0055] When the amount of the third graphite particles contained in the negative electrode material is 25% by mass or less relative to the total mass of the graphite particles, the amount of fine particles derived from the second graphite particles and the third graphite particles is not too large, and the electrolyte can penetrate smoothly. Therefore, the diffusion resistance of lithium ions is small, and the deterioration of the overall battery performance, especially the continuous charge acceptance (pulse charge characteristics), tends to be suppressed. Furthermore, the amount of coarse particles derived from the second graphite particles is not too large, and local expansion and contraction due to charge and discharge within the electrode is suppressed. As a result, peeling of the electrode from the current collector is suppressed, and the cycle characteristics are maintained well. From the viewpoint of the above-mentioned effects, when the negative electrode material of the present disclosure contains the third graphite particles, the amount of the second graphite particles is preferably 25 mass % to 50 mass % with respect to the total mass of the graphite particles.

[0056] In this disclosure, "total mass of graphite particles" means the combined mass of the first graphite particles and the second graphite particles when the negative electrode material contains only the first graphite particles and the second graphite particles as graphite particles, and means the combined mass of the first graphite particles, the second graphite particles, and the graphite particles not corresponding to these when the negative electrode material further contains graphite particles not corresponding to the first graphite particles or the second graphite particles (e.g., third graphite particles).

[0057] In the negative electrode material of the present disclosure, the total mass of the first graphite particles and the second graphite particles, or the total mass of the first graphite particles, the second graphite particles and the third graphite particles, is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 100 mass%, of the total mass of the graphite particles.

[0058] In the present disclosure, the method of mixing two or more types of graphite particles is not particularly limited. For example, they may be mixed using a powder mixer such as a V-type mixer. Alternatively, two or more types of graphite particles may be mixed with other materials when preparing a slurry.

[0059] The particle size, apparent density, compressibility and linseed oil absorption of the negative electrode material (ie, the mixture of graphite particles) are not particularly limited. For example, in the volume-based particle size distribution of the negative electrode material, D10 can be selected from the range of 8 μm to 13 μm, D50 can be selected from the range of 14 μm to 20 μm, and D90 can be selected from the range of 24 μm to 43 μm. The anode material may have a T1 of 0.55 g / cc or more, a T2 of 0.70 g / cc or more, a T3 of 1.00 g / cc or more, and a compression degree of 21 or less. The linseed oil absorption of the negative electrode material can be selected from the range of 45 mL / 100 g to 56 mL / 100 g.

[0060] <Negative electrodes for lithium-ion secondary batteries> The negative electrode for lithium ion secondary batteries (hereinafter also referred to as the negative electrode) of the present disclosure includes a negative electrode material layer containing the above-mentioned negative electrode material and a current collector. The negative electrode for lithium ion secondary batteries may include other components as necessary in addition to the negative electrode material layer containing the above-mentioned negative electrode material and the current collector.

[0061] The method for producing the negative electrode is not particularly limited. For example, a method of preparing a slurry-like negative electrode material composition by kneading a negative electrode material and a binder with a solvent, and applying the slurry to a current collector, a method of forming the negative electrode material composition into a sheet or pellet shape, and integrating the sheet or pellet with a current collector, etc. can be mentioned. Kneading can be performed using a dispersion device such as a stirrer, a ball mill, a super sand mill, or a pressure kneader.

[0062] The binder used to prepare the negative electrode material composition is not particularly limited. Examples of the binder include styrene-butadiene copolymers, polymers of ethylenically unsaturated carboxylic acid esters such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, acrylonitrile, methacrylonitrile, hydroxyethyl acrylate, and hydroxyethyl methacrylate, polymers of ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid, and polymeric compounds having high ionic conductivity such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, and polyacrylonitrile. When the negative electrode material composition contains a binder, the amount of the binder is not particularly limited. The content of the binder may be, for example, 0.5 parts by mass to 20 parts by mass with respect to 100 parts by mass of the total of the negative electrode material and the binder.

[0063] The solvent is not particularly limited as long as it can dissolve or disperse the binder.Specific examples of the solvent include organic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, and γ-butyrolactone.The content of the solvent may be, for example, 60 parts by mass to 150 parts by mass relative to 100 parts by mass of the negative electrode material.

[0064] The negative electrode material composition may contain a thickener. Examples of the thickener include carboxymethyl cellulose or a salt thereof, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid or a salt thereof, alginic acid or a salt thereof, oxidized starch, phosphorylated starch, and casein. When the negative electrode material composition contains a thickener, the amount of the thickener is not particularly limited. The content of the thickener may be, for example, 0.1 to 5 parts by mass relative to 100 parts by mass of the negative electrode material.

[0065] The negative electrode material composition may contain a conductive auxiliary material. Examples of the conductive auxiliary material include carbon materials such as natural graphite, artificial graphite, and carbon black (acetylene black, thermal black, furnace black, etc.), oxides that exhibit conductivity, and nitrides that exhibit conductivity. When the negative electrode material composition contains a conductive auxiliary material, the amount thereof is not particularly limited. The content of the conductive auxiliary material may be, for example, 0.5 parts by mass to 15 parts by mass relative to 100 parts by mass of the negative electrode material.

[0066] The material of the current collector is not particularly limited and can be selected from aluminum, copper, nickel, titanium, stainless steel, etc. The state of the current collector is not particularly limited and can be selected from foil, perforated foil, mesh, etc. In addition, porous materials such as porous metal (foamed metal) and carbon paper can also be used as the current collector.

[0067] When the negative electrode material composition is applied to the current collector to form the negative electrode material layer, the method is not particularly limited, and known methods such as metal mask printing, electrostatic painting, dip coating, spray coating, roll coating, doctor blade, comma coating, gravure coating, and screen printing can be used. After the negative electrode material composition is applied to the current collector, the solvent contained in the negative electrode material composition is removed by drying. The drying can be performed using, for example, a hot air dryer, an infrared dryer, or a combination of these devices. A rolling process may be performed as necessary. The rolling process can be performed using a method such as a flat plate press or a calendar roll.

[0068] When the negative electrode material composition formed into a shape such as a sheet or pellet is integrated with a current collector to form a negative electrode material layer, the integration method is not particularly limited. For example, it can be performed by using a roll, a flat plate press, or a combination of these means. The pressure during integration is preferably, for example, 1 MPa to 200 MPa.

[0069] <Lithium-ion secondary battery> The lithium ion secondary battery of the present disclosure includes the negative electrode for lithium ion secondary batteries of the present disclosure described above (hereinafter also simply referred to as the "negative electrode"), a positive electrode, and an electrolyte solution.

[0070] The positive electrode can be obtained by forming a positive electrode layer on a current collector in the same manner as the negative electrode described above. The current collector can be made of a metal or alloy such as aluminum, titanium, or stainless steel in the form of a foil, a perforated foil, a mesh, or the like.

[0071] The positive electrode material used to form the positive electrode layer is not particularly limited. For example, metal compounds (metal oxides, metal sulfides, etc.) capable of doping or intercalating lithium ions and conductive polymer materials can be mentioned. More specifically, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium manganese oxide (LiMnO 2 ), and their double oxides (LiCo x Ni y Mn z O 2 , x+y+z=1), and a double oxide containing an additive element M' (LiCo a Ni b Mn c M' d O 2 , a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel type lithium manganese oxide (LiMn 2 O 4 ), lithium vanadium compounds, V 2 O 5 , V.O. 2 , MnO 2 , TiO 2 , MoV 2 O 8 , TiS 2 , V 2 S 5 , V.S. 2 , MoS 2 , MoS 3 , Cr 3 O 8 , Cr 2 O 5 , Olivine type LiMPO 4Examples of the positive electrode material include lithium-containing compounds such as (M: Co, Ni, Mn, Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, and porous carbon. The positive electrode material used to form the positive electrode material layer may be one type alone or two or more types.

[0072] The electrolytic solution is not particularly limited, and for example, a solution in which a lithium salt as an electrolyte is dissolved in a non-aqueous solvent (a so-called organic electrolytic solution) can be used. The lithium salt is LiClO 4 , LiPF 6 , LiAsF 6 , LiBF 4 , LiSO 3 CF 3 The lithium salt contained in the electrolyte may be one type alone or two or more types. Examples of non-aqueous solvents include ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, cyclopentanone, cyclohexylbenzene, sulfolane, propane sultone, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, trimethyl phosphate, triethyl phosphate, etc. The non-aqueous solvent contained in the electrolytic solution may be one type alone or two or more types.

[0073] The state of the positive electrode and the negative electrode in the lithium ion secondary battery is not particularly limited. For example, they may be in the form of a laminate consisting of a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode as necessary. The laminate may be in a spirally wound state, or may be in a state in which a plurality of laminates are further laminated.

[0074] The separator is not particularly limited, and for example, a resin nonwoven fabric, cloth, microporous film, or a combination thereof can be used. Examples of the resin include those mainly composed of polyolefins such as polyethylene and polypropylene. In the structure of the lithium ion secondary battery, if the positive electrode and the negative electrode are not in direct contact with each other, the separator does not need to be used.

[0075] The shape of the lithium ion secondary battery is not particularly limited, and examples thereof include laminate type batteries, paper type batteries, button type batteries, coin type batteries, stacked type batteries, cylindrical batteries, and square batteries.

[0076] The lithium ion secondary battery of the present disclosure has excellent output characteristics and is therefore suitable as a large-capacity lithium ion secondary battery for use in electric vehicles, power tools, power storage devices, etc. In particular, it is suitable as a lithium ion secondary battery for use in electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., which require high-current charging and discharging to improve acceleration performance and brake regeneration performance. EXAMPLES

[0077] The present disclosure will be described in detail below with reference to examples. However, the present disclosure is not limited to the following examples, and can be appropriately modified and implemented within the scope of the present disclosure.

[0078] <Examples 1 to 5, Comparative Examples 1 to 7> [Preparation of the first graphite particles] A mixture was obtained by mixing 100 parts by mass of spherical natural graphite (secondary particles consisting of multiple natural graphite particles) with an average particle size of 16 μm with 6 parts by mass of coal tar pitch (softening point 90° C., residual carbon rate (carbonization rate) 50%). The mixture was then heated to 950° C. at a heating rate of 20° C. / hour under nitrogen flow and held at 950° C. (sintering temperature) for 1 hour to obtain graphite particles coated with low crystalline carbon. The obtained graphite particles were crushed with a cutter mill and then sieved with a 300 mesh sieve, and the undersieve portion was used as graphite particles (sample number 1).

[0079] Graphite particles (sample numbers 2 to 11) were produced by changing the amount of carbon coating or the type of spherical natural graphite used as a raw material in the production of graphite particles (sample number 1). The obtained graphite particles (sample numbers 1 to 11) were subjected to measurement of particle diameter (D0.1, D10, D50 and D90) and N 2 Specific surface area measurement, oil absorption measurement, R value measurement, CO 2 Measurement of adsorption amount, average interplanar spacing d 002 Measurements of the particle diameter, circularity, apparent density, and compressibility were carried out. The physical property values ​​are shown in Table 1. The amount of carbon coating (parts by mass) in Table 1 means the amount of coal tar pitch (parts by mass) relative to 100 parts by mass of spherical natural graphite.

[0080] [Preparation of secondary graphite particles] 43 parts by mass of coke powder having an average particle size of 10 μm, 18.5 parts by mass of coal tar pitch, 18.5 parts by mass of silicon carbide, and 20 parts by mass of spherical natural graphite having an average particle size of 20 μm were mixed and stirred at 100 ° C for 1 hour to obtain a mixture. Next, this mixture was pulverized to a particle size of 25 μm, and the obtained pulverized powder was placed in a mold and molded into a rectangular parallelepiped. The obtained rectangular parallelepiped was heat-treated at 1000 ° C in a nitrogen atmosphere, and then fired at 2800 ° C to graphitize the graphitizable components to obtain a graphite molded body. The obtained graphite molded body was roughly crushed with a hammer and then pulverized with a pin mill to obtain graphite particle powder. Furthermore, it was sieved with a 300 mesh sieve, and the undersieve portion was taken as graphite particles (sample number 12). The obtained graphite particles (sample number 12) were subjected to measurement of particle size (D0.1, D10, D50 and D90) and CO 2 The amount of adsorption was measured. The physical properties are shown in Table 1.

[0081] [Preparation of negative electrode material] Graphite particles (sample numbers 2 to 11) as the first graphite particles and graphite particles (sample number 12) as the second graphite particles were mixed in a V-type mixer for 2 hours to prepare negative electrode materials of Examples 1 to 5 and Comparative Examples 2 to 7. In preparing each negative electrode material, the blending amount of the second graphite particles was 35 mass% with respect to the total mass of the graphite particles. In addition, graphite particles (sample number 1) not mixed with graphite particles (sample number 12) were used as Comparative Example 1. The particle size (D10, D50, and D90) of the obtained negative electrode material was measured, the apparent density was measured, the compression degree was calculated, and the N 2 The specific surface area and oil absorption were measured. The physical properties are shown in Table 1.

[0082] [Table 1]

[0083] [Particle size measurement] The sample was dispersed in purified water together with a 0.2% by mass surfactant (product name: Ribonol T / 15, Lion Corporation) and the resulting dispersion was placed in the sample water tank of a laser diffraction particle size distribution analyzer (SALD-3000J, Shimadzu Corporation). Next, the solution was circulated with a pump while being subjected to ultrasonic waves (pump flow rate was 65% from the maximum), the amount of water was adjusted so that the absorbance was 0.10 to 0.15, and the volumetric particle size distribution was measured. From the volume-based particle size distribution obtained, particle sizes corresponding to D0.1, D10, D50 and D90 of the sample were obtained.

[0084] [Measurement of loose apparent density by static method] Capacity 30cm 3The sample was allowed to fall freely into a measuring cylinder (Tsutsui Rikagaku Kikai Co., Ltd., JIS K-5101 compliant specifications) using a funnel with a 500 μm mesh. The sample was allowed to overflow from the measuring cylinder, and the sample was leveled off at the mouth of the measuring cylinder to reduce the volume of the sample to 30 cm. 3 The mass of the measuring cylinder containing the sample was measured, and the mass of the sample was calculated by subtracting the mass of the measuring cylinder from the measured mass. The loose apparent density (T1) of the sample was calculated by the following formula. T1 = {(mass of sample) / (volume of sample: 30 cm 3 )}

[0085] [Measurement of apparent density using the 30 and 250 tap methods] Capacity 150cm 3 A 100 cm sample was placed in a graduated flat-bottom test tube (Kuramochi Scientific Instruments Manufacturing Co., Ltd., KRS-406). 3 The test tube was then stopped up. The mass and volume of the sample were measured after the test tube was dropped 30 times from a height of 5 cm. The apparent density (T2) of the sample was calculated using the following formula: T2 = {(mass of sample) / (volume of sample after 30 taps)} The apparent density T3 of the sample by the 250 tap method was measured in the same manner as T2, except that the number of drops from a height of 5 cm was 250.

[0086] [Calculation of compression degree] The compressibility of the sample was calculated from the measured values ​​of the loose apparent density (T1) by the static method, the apparent density (T2) by the 30 tapping method, and the apparent density (T3) by the 250 tapping method, according to the following formula. Compression ratio (%) = [(T2-T1) / T3] x 100

[0087] [N 2 Measurement of specific surface area Sample N 2 The specific surface area was calculated by the BET method using a high-speed specific surface area / pore distribution analyzer (FlowSorbIII, Shimadzu Corporation), after pretreatment drying (at 200°C for 2 hours or more) and then measuring the nitrogen adsorption at liquid nitrogen temperature (77 K) using a single-point method.

[0088] [Measurement of linseed oil absorption] The linseed oil absorption of the samples was measured according to the method described in JIS K6217-4:2008 "Carbon black for rubber use - Fundamental properties - Part 4: Determination of oil absorption" using linseed oil (Kanto Chemical Co., Ltd.) instead of dibutyl phthalate (DBP) as the reagent liquid. Specifically, linseed oil was titrated into the sample using a constant speed burette, and the change in viscosity characteristics was measured using a torque detector. The amount of linseed oil added per unit mass of the sample that corresponds to 70% of the maximum torque generated was taken as the linseed oil absorption (mL / 100g). The measurement device used was an absorption measurement device manufactured by Asahi Research Institute Co., Ltd.

[0089] [R-value measurement] The R value of the sample was determined by Raman spectroscopy under the following conditions. -1 The intensity Ig of the maximum peak near 1360 cm -1 The intensity ratio (Id / Ig) was calculated based on the intensity Id of the maximum peak in the vicinity of the peak. The Raman spectroscopy was performed using a laser Raman spectrophotometer (model number: NRS-1000, JASCO Corporation) by irradiating a laser beam onto a sample plate set so that the sample was flat. The measurement conditions were as follows: Laser light wavelength: 532nm Wavenumber resolution: 2.56cm -1 Measurement range: 1180cm -1 ~1730cm -1 Peak Search: 0.5° / min

[0090] [CO 2 Measurement of adsorption amount] Sample CO 2 The amount of adsorption was measured using a Belsorp II manufactured by Microtrac-Bell Co., Ltd. The Belsorp II manufactured by Microtrac-Bell Co., Ltd. was used as the pretreatment device. 2 The adsorption amount was measured at a temperature of 273K and a relative pressure of P / P 0= 0.98 to 0.99 (P = equilibrium pressure, P 0 = saturated vapor pressure) was used. Pretreatment consisted of heating to 250°C at 5°C / min in a vacuum of 1 Pa or less, holding for 10 minutes, then heating to 350°C at 3°C / min, holding for 210 minutes. After that, heating was stopped and the sample was cooled to room temperature. The relative pressures used to measure the amount of adsorption were as shown in Table 2 below. The above method was used to measure the CO concentration of the standard alumina powder (BCR-171, No. 0446, Institute for Reference Materials and Measurements). 2 The amount of adsorption was measured to be 0.40 cm 3 / g.

[0091] [Table 2]

[0092] [Average spacing d 002 Measurement of Average interplanar spacing of sample d 002 was measured by X-ray diffraction. Specifically, the sample was filled into the concave part of a quartz sample holder and set on the measurement stage, and measurements were performed using a wide-angle X-ray diffractometer (Rigaku Corporation) under the following conditions. Radiation source: CuKα ray (wavelength=0.15418nm) Output: 40kV, 20mA Sampling width: 0.010° Scanning range: 10°~35° Scan speed: 0.5° / min

[0093] [Measurement of average circularity] The circularity of the sample was measured using a wet flow particle size and shape analyzer (Malvern Panalytical FPIA-3000). The measurement temperature was 25°C, the sample concentration was 10 mass%, and the number of particles counted was 10,000. Water was used as the dispersion solvent. It is preferable to disperse the sample powder before measuring the circularity of the sample. For example, the sample can be dispersed using ultrasonic dispersion, a vortex mixer, etc. The treatment conditions are adjusted in consideration of the strength of the sample to be measured in order to suppress the influence of particle collapse or particle destruction of the sample.

[0094] [Preparation of negative electrode] Using the negative electrode materials prepared in the examples and comparative examples, sample electrodes (negative electrodes) were prepared according to the following procedure. First, carboxymethyl cellulose (CMC) as a thickener and styrene butadiene rubber (SBR) as a binder were added to the negative electrode material. The mass ratio of these was negative electrode material:CMC:SBR=98:1:1. Purified water, which was a dispersion solution, was added to this and kneaded to obtain a slurry. A predetermined amount of this slurry was applied substantially evenly and homogeneously to a rolled copper foil with an average thickness of 10 μm, which was a current collector for the negative electrode (application amount: 10.0 mg / cm 2 ) Then, roll press it to 1.6g / cm 3 The electrode density was adjusted to obtain a rolled copper foil with a negative electrode layer formed on one side. This rolled copper foil was punched into a disk shape with a diameter of 14 mm to prepare a sample electrode (negative electrode). Using the prepared sample electrode, the electrode permeation rate of the electrolyte and the electrode swelling ratio were measured by the following method. The results are shown in Table 3.

[0095] [Electrolyte penetration rate into electrodes] The electrolyte (LiPF 6 0.02 ml of electrolyte (EC+DMC, Kishida Chemical Co., Ltd.) was dropped using a microsyringe, and the time until the electrolyte disappeared from the negative electrode coating was measured.

[0096] [Electrode swelling rate] The negative electrode layer of the sample electrode was placed in an electrolyte (LiPF 6 The change in layer thickness before and after immersion was measured with a micrometer, and the swelling ratio was calculated using the following formula. Swelling rate (%) = {(thickness after immersion - thickness before immersion) / thickness before immersion} x 100

[0097] [Preparation of lithium-ion secondary batteries] The prepared sample electrode (negative electrode), separator, and counter electrode (positive electrode) were placed in a coin-type battery container in this order, and an electrolyte was injected to prepare a coin-type lithium-ion secondary battery. The electrolyte was a mixed solvent of EC (ethylene carbonate) and EMC (ethyl methyl carbonate) (EC:EMC volume ratio 3:7), with 0.5 mass% vinylene carbonate (VC) added to the total amount of the mixed solvent, and LiPF 6 was dissolved to a concentration of 1 mol / L. Metallic lithium was used as the counter electrode (positive electrode). A polyethylene microporous film having a thickness of 20 μm was used as the separator. The lithium ion secondary battery thus produced was used to evaluate the initial charge / discharge characteristics, low-temperature charge characteristics, high-temperature storage characteristics, and discharge load characteristics by the following methods. The results are shown in Table 3.

[0098] (Evaluation of initial charge / discharge characteristics) The lithium-ion secondary battery was then charged at a current of 0.2 C and a voltage of 0 V (V vs. Li / Li + ), and then constant voltage charging (CV charging) was performed at 0 V until the current value reached 0.02 C. The capacity at this time was defined as the initial charging capacity (CC / CV charging). Next, after a 30-minute break, the battery was charged at a current value of 0.2 C to 1.5 V (V vs. Li / Li + The capacity at this time was defined as the initial discharge capacity. The irreversible capacity was calculated by subtracting the initial discharge capacity from the initial charge capacity, and the ratio of the initial discharge capacity to the initial charge capacity was calculated as the initial efficiency. Note that the unit of current, "C," means "current (A) / battery capacity (Ah)." Irreversible capacity [mAh / g] = (Initial charge capacity) - (Initial discharge capacity) Initial efficiency [%] = (initial discharge capacity) / (initial charge capacity) x 100

[0099] (Evaluation of low-temperature charging characteristics) The fabricated lithium-ion secondary battery was placed in a thermostatic chamber set at 25°C, and the current was 0.2C and the voltage was 0V (V vs. Li / Li + ), then constant voltage charging (CV charging) was performed at 0 V until the current value reached 0.02 C. After a 30-minute break, the battery was charged to 1.5 V (V vs. Li / Li) at a current value of 0.2 C. + This charge / discharge cycle was counted as one cycle, and a second charge / discharge cycle was then performed. After that, the lithium-ion secondary battery was placed in a thermostatic chamber set at -30°C, and the voltage was measured at 0 V (V vs. Li / Li + ), and then constant voltage charging (CV charging) was performed at 0 V until the current value reached 0.02 C. The low temperature charge acceptance was determined from the ratio of the CC charge capacity when charging was performed at -30°C to the CC / CV charge capacity when charging was performed at -30°C described above. Low temperature charge acceptance [%] = (CC charge capacity at -30°C) / (CC / CV charge capacity at -30°C) x 100

[0100] (Evaluation of high temperature storage properties) The fabricated lithium-ion secondary battery was placed in a thermostatic chamber set at 25°C, and the current was 0.2C and the voltage was 0V (V vs. Li / Li + ), then constant voltage charging was performed at 0 V until the current value reached 0.02 C. After a 30-minute break, the battery was charged at a current value of 0.2 C to 1.5 V (V vs. Li / Li + This charge / discharge cycle was counted as one cycle, and after the second charge / discharge cycle, Current value 0.2C and voltage 0V (V vs. Li / Li + ), and then constant voltage charging was performed at 0 V until the current value reached 0.02 C. The battery was then placed in a thermostatic chamber set at 60° C. and stored for 5 days. After that, place it in a thermostatic chamber set at 25°C and leave it for 60 minutes. Then, at a current value of 0.2C, the voltage is 1.5V (V vs. Li / Li + ) The battery was then charged and discharged under the same conditions as in the first cycle. The high temperature storage maintenance rate and the high temperature storage recovery rate were calculated from the following formula. High temperature storage retention rate [%] = (After storing at 60°C for 5 days, first discharge capacity at 25°C) / (second cycle discharge capacity at 25°C) x 100 High temperature storage recovery rate [%] = (2nd discharge capacity at 25°C after storage at 60°C for 5 days) / (2nd cycle discharge capacity at 25°C) × 100

[0101] (Evaluation of discharge load characteristics) The fabricated lithium-ion secondary battery was placed in a thermostatic chamber set at 25°C, and the current was 0.2C and the voltage was 0V (V vs. Li / Li + ), then constant voltage charging was performed at 0 V until the current value reached 0.02 C. After a 30-minute break, the battery was charged at a current value of 0.2 C to 1.5 V (V vs. Li / Li + This charge / discharge cycle was counted as one cycle, and a second charge / discharge cycle was then performed. Next, the current is 0.2C and the voltage is 0V (V vs. Li / Li + ), then constant voltage charging at 0 V until the current value reached 0.02 C, and charging the battery to 1.5 V (V vs. Li / Li) at a current value of 4 C. + ) constant current discharge was performed. The discharge load was calculated from the following formula: Discharge load [%] = (discharge capacity obtained at a current value of 4 C) / (discharge capacity in the second cycle obtained at a current value of 0.2 C) x 100

[0102] [Preparation of negative electrodes for evaluating cycle characteristics and pulse charging characteristics] Using the negative electrode materials prepared in the examples and comparative examples, sample electrodes (negative electrodes) were prepared according to the following procedure. First, carboxymethyl cellulose (CMC) as a thickener and styrene butadiene rubber (SBR) as a binder were added to the negative electrode material. The mass ratio of these was negative electrode material / CMC / SBR=98 / 1 / 1. Purified water, which was a dispersion solution, was added to this and kneaded to form a slurry. A predetermined amount of this slurry was applied substantially evenly and homogeneously to a rolled copper foil with an average thickness of 10 μm, which was the current collector for the negative electrode (application amount: 10.0 mg / cm 2 ) Then, roll press it to 1.6g / cm 3 The electrode density was adjusted to obtain a rolled copper foil with a negative electrode layer formed on one side. This rolled copper foil was punched out to a size of 2.5 cm x 12 cm to prepare a sample electrode (negative electrode).

[0103] [Preparation of lithium-ion secondary batteries for evaluation of cycle characteristics and pulse charging characteristics] The fabricated sample electrode (negative electrode) was folded, and the folded separator and counter electrode (positive electrode) were placed in the folded electrode, and an electrolyte was injected to fabricate a lithium-ion secondary battery. The electrolyte was a mixed solvent of EC (ethylene carbonate) and EMC (ethyl methyl carbonate) (the volume ratio of EC to EMC was 3:7), with 0.5 mass% of vinylene carbonate (VC) added to the total amount of the mixed solution, and LiPF 6 The lithium ion secondary battery was dissolved to a concentration of 1 mol / L. The counter electrode (positive electrode) was an electrode (1.5 cm x 4 cm) with a mass ratio of 90 / 5 / 5 of ternary (Ni, Co, Mn) lithium oxide / conductive material / PVDF (polyvinylidene fluoride). The separator was a polyethylene microporous membrane with a thickness of 20 μm. The lithium ion secondary battery was used to evaluate the cycle characteristics and pulse charge characteristics by the following method. The results are shown in Table 3.

[0104] [Evaluation of cycle characteristics] The cycle characteristics of the produced lithium ion secondary battery were evaluated as follows. First, the battery was charged at a constant current of 2C at 45°C with a cut-off voltage of 4.2V, and then charged at a constant voltage of 0.02C from the time the battery reached 4.2V. After a 30-minute pause, the battery was discharged at a constant current of 2C at 25°C with a cut-off voltage of 2.7V, and the discharge capacity was measured (discharge capacity at the first cycle). The above charge and discharge constitute one cycle, and the battery was discharged 500 times, and the discharge capacity was measured after the 300th cycle and the 500th cycle. The discharge capacity retention rate (%) was calculated from the following formula. Discharge capacity retention rate [%] = (discharge capacity after 300 cycles or 500 cycles) / (discharge capacity at the first cycle) × 100

[0105] [Evaluation of pulse charging characteristics] The pulse charge characteristics were determined from the state of Li precipitation. The lithium-ion secondary battery was charged at a constant current of 1C at 25°C with a charge cut-off voltage of 4.2V, and then charged at a constant voltage of 0.02C from the time the charge reached 4.2V. After a 30-minute break, the battery was discharged at a constant current of 1C at 25°C with a cut-off voltage of 2.7V. This charge / discharge cycle was counted as one cycle, and three charge / discharge cycles were performed. Next, the battery was placed in a thermostatic chamber set at -30°C and left for 60 minutes, then charged for 5 seconds at a current value equivalent to 20C. The battery was then disassembled and the state of Li precipitation was confirmed using a SEM (Keyence Corporation, SU3500). When no Li precipitation was observed, it was determined that the pulse charging characteristics were excellent.

[0106] [Table 3]

[0107] As is clear from the results shown in Table 3, Examples 1 to 5, in which the graphite particles contained in the negative electrode material satisfied the specified conditions, maintained high charge / discharge efficiency compared to Comparative Examples 1 to 7, in which the graphite particles contained in the negative electrode material did not satisfy the specified conditions, and also had excellent low-temperature charging characteristics, high-temperature storage characteristics, discharge load characteristics, and pulse charging characteristics. The presumed mechanism for the performance improvement is explained below. The first graphite particles contained in the negative electrode material are relatively fine particles, and the second graphite particles are relatively large (coarse) particles and finer (finer) than the first graphite particles. Therefore, when these graphite particles are blended, the gaps between the particles are mutually filled, and the filling state of the resulting negative electrode coating film can be well controlled. The filling state can be controlled by the physical properties of the first graphite particles and the second graphite particles. When the physical properties of the first graphite particles and the second graphite particles satisfy predetermined conditions, the pressing force can be applied uniformly to the inside of the coating film in the pressing process during the production of the negative electrode. Therefore, the density variation in the thickness direction of the coating film is reduced, and the electrolyte can be smoothly penetrated. As a result, the battery performance is improved. In addition, the hardness of the graphite particles described below is also a factor that contributes to the improvement of the battery performance.

[0108] [Evaluation of electrode pressability] Sample electrodes were prepared by the same method as described above using the graphite particles of sample numbers 1, 2, 3, 6, and 12, which were constituted in Examples 1, 2, and 3, and Comparative Example 2, alone. Using the sample electrodes, pressing was carried out at arbitrary hydraulic pressures (t) that were varied while the roll gap of the roll press was fixed. The thickness of each electrode pressed at each hydraulic pressure was measured, and the electrode density (g / cm 3 ) was calculated to evaluate the electrode pressability. The results are shown in Figures 1 and 2.

[0109] As shown in Figures 1 and 2, the electrode pressability of sample No. 1, which is graphite particles coated with low crystalline carbon, shows a smaller increase in electrode density with an increase in roll press oil pressure than that of sample No. 6, which is graphite particles not coated with low crystalline carbon. In addition, when comparing sample No. 2 and sample No. 3, which have different particle sizes, sample No. 3, which has a smaller particle size, shows a smaller increase in electrode density and has harder particles than sample No. 2. Furthermore, when comparing sample No. 1, 2, and 3, which corresponds to the first graphite particles, with sample No. 12, which corresponds to the second graphite particles, sample No. 1, 2, and 3 shows a smaller increase in electrode density and has harder particles than sample No. 12. From the above results, it can be seen that the hardness of the graphite particles can be controlled by coating the graphite particles or by changing the particle diameter of the graphite particles. In other words, by selecting first graphite particles with a desired hardness and combining them with second graphite particles with a different hardness, the hardness as a negative electrode material can be controlled, particle deformation due to the pressing force when pressing the electrode with high pressure can be suppressed, a permeation path for the electrolyte can be secured, and the electrolyte can be smoothly permeated. As a result, it is possible to contribute to improving low-temperature charging characteristics, high-temperature storage characteristics, discharge load characteristics, and pulse charging characteristics while maintaining high charge and discharge efficiency.

[0110] <Examples 6 to 9, Comparative Example 8> A negative electrode material was produced by using sample number 1 as the first graphite particles and sample number 12 as the second graphite particles, and varying the blending amount of the second graphite particles. The obtained negative electrode material was used to evaluate the electrode characteristics and battery characteristics in the same manner as in Example 1. The results are shown in Table 4.

[0111] [Table 4]

[0112] As shown in Table 4, Examples 1 and 6 to 9, in which the blending amount of the second graphite particles is 55 mass% or less, tend to have better battery charge / discharge characteristics than Comparative Example 8, in which the blending amount of the second graphite particles exceeds 55 mass%. Although the exact reason is unclear, it is thought that the amount of fine particles derived from the second graphite particles that fill the voids of the first graphite particles is not too large, allowing the electrolyte to penetrate smoothly. Another reason is that the swelling rate of the electrode due to the electrolyte is suppressed, thereby keeping the impedance low.

[0113] <Examples 10 to 12, Comparative Examples 9 to 11> Graphite particles (sample number 13) were prepared in the same manner as in the preparation of graphite particles (sample number 12), except that the D50 of the graphite particles was adjusted to 20 μm.

[0114] 100 parts by mass of graphite particles (sample number 12) were mixed with 6 parts by mass of coal tar pitch (softening point 90°C, residual carbon rate (carbonization rate) 50%). Next, the mixture was heated to 950°C at a heating rate of 20°C / hour under nitrogen flow, and held at 950°C (sintering temperature) for 1 hour to obtain carbon layer-coated graphite particles. The obtained carbon layer-coated graphite particles were crushed with a cutter mill and then sieved through a 300 mesh sieve, and the undersieve portion was obtained as graphite particles (sample number 14).

[0115] Graphite particles (sample number 15) were produced in the same manner as in the production of graphite particles (sample number 12), except that graphitization was carried out in the state of pulverized powder rather than in the state of a molded block.

[0116] Graphite particles (sample number 16) were prepared in the same manner as in the preparation of graphite particles (sample number 12), except that the D50 of the graphite particles was adjusted to 27 μm.

[0117] Graphite particles (sample number 17) were prepared in the same manner as in the preparation of graphite particles (sample number 14), except that graphite particles (sample number 13) were used as the graphite particles to be the core material before being coated with a carbon layer.

[0118] Graphite particles (sample number 18) were produced in the same manner as in the production of graphite particles (sample number 16), except that graphitization was carried out in the state of pulverized powder rather than in the state of a molded block.

[0119] A negative electrode material was produced using sample number 1 as the first graphite particles and sample numbers 12 to 18 as the second graphite particles, and the physical properties were measured. Furthermore, the obtained negative electrode material was used to evaluate the electrode characteristics and battery characteristics in the same manner as in Example 1. The results are shown in Table 5.

[0120] [Table 5]

[0121] As shown in Table 5, Examples 1 and 10 to 12, in which the negative electrode material contains second graphite particles satisfying the specified conditions, maintained high charge / discharge efficiency compared to Comparative Examples 9 to 11, in which the negative electrode material does not contain second graphite particles satisfying the specified conditions, and also had excellent low-temperature charging characteristics, high-temperature storage characteristics, discharge load characteristics, and pulse charging characteristics.

[0122] In the following examples, a negative electrode material containing third graphite particles in addition to the first and second graphite particles was examined.

[0123] <Examples 13 to 19> The graphite particles having the sample numbers and amounts shown in Table 6 were designated as the first graphite particles, the second graphite particles, and the third graphite particles, respectively, and were mixed to prepare a negative electrode material. Furthermore, the electrode characteristics and battery characteristics were evaluated in the same manner as in Example 1 using the obtained negative electrode material. In Examples 13 to 19, the electrode density was set to 1.75 g / cm in the measurement of the electrode permeation rate, the evaluation of the initial charge / discharge characteristics, and the cycle characteristics. 3 An additional evaluation was carried out when the electrode density was 1.75 g / cm 3 The negative electrode was prepared by adjusting the hydraulic pressure of the roll press described above. The results are shown in Table 6.

[0124] [Table 6]

[0125] As shown in Table 6, Examples 13 to 19, which contained third graphite particles in addition to the first and second graphite particles, maintained high charge / discharge efficiency compared to Examples 1 and 8, which did not contain the third graphite particles, while also exhibiting excellent low-temperature charging characteristics, high-temperature storage characteristics, and discharge load characteristics. Examples 13 to 19, which contain third graphite particles in addition to the first and second graphite particles, show a high electrode density of 1.75 g / cm 3 ) and maintained high capacity and efficiency while also exhibiting excellent cycle characteristics.

[0126] [Measurement of electrode resistance] The negative electrodes prepared in Examples 14, 17, 19, 1 and 8 (electrode density: 1.6 g / cm 3 and 1.75 g / cm 3 ) was used to measure the electrode resistance. For the measurements, an electrode resistance measurement system (RM2610) from Hioki E.E. Corporation was used. By using this measurement system, it is possible to measure the negative electrode material layer resistance and the interface resistance (contact resistance between the current collector and the negative electrode material layer) in the negative electrode separately. The smaller the electrode resistance of the negative electrode, the better the low-temperature charging characteristics, high-temperature storage characteristics, and discharge load characteristics are while maintaining high charge / discharge efficiency. The results are shown in Table 7.

[0127] [Table 7]

[0128] As shown in Table 7, the electrode resistances (negative electrode material layer resistance and interface resistance) of Examples 14, 17, and 19, which contain the third graphite particles, are lower than those of Examples 1 and 8, which do not contain the third graphite particles. The above results show that the electrode resistance can be reduced by adding the third graphite particles to the negative electrode material.

Claims

1. First graphite particles satisfying the following conditions 1A and 1B; Second graphite particles satisfying the following conditions 2A and 2B, the amount of the second graphite particles is 10% by mass to 55% by mass based on the total mass of the graphite particles; A negative electrode material for a lithium ion secondary battery, wherein the first graphite particles are secondary particles composed of a plurality of natural graphite particles, and at least a portion of the surface of the first graphite particles is coated with a carbon material having a lower crystallinity than the natural graphite particles. Condition 1A: The loose apparent density T1 measured by the static method is 0.60 g / cc or more, the apparent density T2 measured by the 30 tapping method is 0.80 g / cc or more, the apparent density T3 measured by the 250 tapping method is 1.00 g / cc or more, and the value of the compressibility represented by the following formula is 19% or less. Compressibility (%) = [(T2 - T1) / T3] x 100 Condition 1B: Linseed oil absorption is 40 mL / 100 g to 55 mL / 100 g Condition 2A: D0.1 in the volume-based particle size distribution is 5 μm or less Condition 2B: Linseed oil absorption is 55 mL / 100 g to 75 mL / 100 g

2. 2. The negative electrode material for lithium ion secondary batteries according to claim 1, wherein the first graphite particles have a volume-based particle size distribution of D10 of 7 μm to 13 μm and D90 of 14 μm to 25 μm.

3. 2. The negative electrode material for lithium ion secondary batteries according to claim 1, wherein D0.1 in the volume-based particle size distribution of the first graphite particles is greater than 5 μm.

4. Further comprising third graphite particles satisfying the following conditions 3A and 3B:

2. The negative electrode material for lithium ion secondary batteries according to claim 1, wherein the third graphite particles are secondary particles composed of a plurality of natural graphite particles, and at least a portion of the surface of the third graphite particles is coated with a carbon material having a lower crystallinity than the natural graphite particles. Condition 3A: In the volume-based particle size distribution, the ratio of D50 of the third graphite particles to D50 of the first graphite particles (D50 of the third graphite particles / D50 of the first graphite particles) is in the range of 0.55 to 0.

75. Condition 3B: Linseed oil absorption is 40 mL / 100 g to 55 mL / 100 g

5. The negative electrode material for lithium ion secondary batteries according to claim 4, wherein the amount of the third graphite particles is 10% by mass to 25% by mass based on the total mass of the graphite particles.

6. A negative electrode for a lithium ion secondary battery comprising: a negative electrode layer containing the negative electrode material according to any one of claims 1 to 5; and a current collector.

7. A lithium ion secondary battery comprising the negative electrode for lithium ion secondary batteries according to claim 6, a positive electrode, and an electrolyte solution.

Citation Information

Patent Citations

  • Negative electrode for lithium secondary battery, and negative electrode active material

    JP2007324067A

  • Carbon material for negative electrode of lithium-ion secondary battery, negative electrode mixture for lithium-ion secondary battery using the same, and lithium-ion secondary battery

    JP2009245613A

  • Anode active material for lithium-ion secondary battery and anode

    JP2010092649A

  • Negative electrode material for lithium ion secondary battery and manufacturing method thereof, negative electrode for lithium ion secondary battery and lithium ion secondary battery

    JP2020177932A

  • Method for manufacturing negative electrode material for lithium ion secondary battery, negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2023073103A